A study on the impact of service quality in EPF / Syaratul Ain Abd Aziz - Abd Aziz, Syaratul Ain (2008)
This research paper is study on the impact of service quality in Employees Provident Fund (EPF) at Jalan Raja Laut, Kuala Lumpur and the purpose of this study is to measure the level of satisfaction of customers towards EPF services. This study also will identify the overall service quality level that customer perceived when they doing any transaction with EPF. A total of 50 respondents were selected to answer questionnaires and the findings can be concluded to identify the level of satisfaction of customer perceived and how the organization should improve their services.